PROBLEM ASPECTS OF THE LEGAL ADJUSTING ARE IN CREDIT-FINANCIAL TO THE SPHERE OF UKRAINE - Bilko, Oleksandr P.; Gavrylishyn, Anatoliy P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the article considers theoretical and legal issues of regulation of financial and credit relations, as well as the prevention of crimes in the field of lending. Emphasis is placed on the complexity of regulating these relations, which is reflected in various areas of law and legislation of Ukraine. Methods: part of the norms of criminal procedure law, administrative, financial, civil, economic and other branches of law, which regulate the sphere of credit relations, is analyzed. Results: emphasis is placed on the expediency of improving the legislation of Ukraine in the field of credit relations, and bringing it into line with European standards. Discussion: problems of legal regulation of financial and credit relations, and prevention of crimes in this area.